Morphometric analysis of the fifth lumbar vertebra (L5): Anatomical dimensions and clinical implications in South Indian population - Nandini Bhat; Lakshmisha Rao; Ashwija Shetty; Souhardya Das; Nom Bhukya Kumar Naik; Vanishri Nayak; Sushma Prabhath; Kurian Alapatt; Suhani Sumalatha (Translational Research in Anatomy)
Background: The anatomical features of L5, including its size, shape, and articulation with the sacrum, make it a crucial structure in weight transfer and spinal stability. Understanding its morphometry is vital for diagnosing and treating pathologies associated with the lumbar spine. This study aims to provide normative data on the morphological and morphometric dimensions of the fifth lumbar vertebra (L5) and discover its clinical implications, assisting in preoperative planning for clinicians, including radiologists and spine surgeons. Methods: Anatomical measurements of fifty dry L5 vertebrae including dimensions of the transverse processes, articular facets, body of the vertebra, and intervertebral foramen, were recorded. Statistical analysis was performed to assess correlations and differences in morphometric data. Results: Body of the vertebra: The mean anteroposterior and transverse diameters of the superior and inferior surfaces of the vertebral body were 3.35 ± 0.41 cm and 4.74 ± 1.39 cm (superior) and 3.33 ± 0.68 cm and 3.78 ± 1.72 cm (inferior), respectively. Significant differences were noted in the transverse diameter between the superior and inferior surfaces. Articular Facets: The superior articular facets were predominantly quadrilateral (46 %), followed by pyramidal (30 %). The inferior facets were most commonly circular (48 %). Significant differences were observed in the distance from the spinous process to the inferior articular facets. Intervertebral Foramen: The anteroposterior length of the intervertebral notch on the right and left sides was significantly variable. Transverse Processes: The mean distance between the tips of the right and left transverse processes was 7.92 ± 0.92 cm. Weak positive correlations were observed between the distance from the spinous process to the transverse processes. Conclusion: The study provides comprehensive morphometric data on the fifth lumbar vertebra, emphasizing important anatomical dimensions that are vital for understanding spinal health and guiding clinical interventions. These findings will aid in the preoperative planning for spine surgeries and the management of lumbar spine disorders. Further research with larger and more diverse samples is recommended to validate and expand these findings.